SISTEM LOGISTIK DI INDONESIA: TINJAUAN KELEMBAGAAN DAN SISTEM INFORMASI - Sudrajat, Asep; Hertina, Dede; Dyahrini, Wien (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The purpose of writing this article is to identify and elaborate on the institutional and logistical information systems, services, and benefits that stakeholders can obtain, as well as the challenges and obstacles that occur, and what solutions can be taken so that the existing logistics system becomes efficient in terms of time, cost, and business processes. The approach taken by the author is through literature review and gathering information from relevant parties and elaborating on the institutions and logistical information systems currently implemented. This study shows that there are several information systems related to the digitization of logistics processes, both developed by government agencies (as authorities) and by companies independently. The logistics information systems currently in operation are relatively integrated (through the National Logistics Ecosystem /NLE) among stakeholders such as Customs, quarantine, Port Authorities, financial services and banking, the Ministry of Transportation (InaPortNet, SIMLALA, SITOLAUT, SIJUKA), the Ministry of Trade (Inatrade), the Ministry of Industry, and the Ministry of Finance (INSW and NLE).